Benthic macrofauna and the limnological parameters of a first-order stream in Atlantic Forest of Brazilian Northeast - Cunha,Janaina Câmara Siqueira da (2014)
AIM: The present study aimed to elucidate if the water physical and chemical parameters from a first order stream of Biological Reserve of Saltinho from south Pernambuco induces in the distribution and abundance of benthic macroinvertebrates. METHODS: Both limnological parameters (pH-value, electrical conductivity, water temperature, turbidity, salinity and dissolved oxygen) and structural variables of aquatic habitat (substrate, food availability and flow velocity) influence the macroinvertebrates community structure. The creek is very small, with an approximate width of 1-3 m and a depth of 0.5 m. It was used a Surber sampler (100 mm) in three stretch of the creek, each one with two sampling units (s.u.) totaling six s.u. distant 50 m, with a sampling effort of five minutes per s.u.. The measurer multiparameter was used in order to obtain the water analysis (limnological parameters). RESULTS: From 11 taxa of macroinvertebrates found no significant correlation (p<0.05) was presented with pH-value, water temperature and salinity, but some taxa showed with electrical conductivity (EC), turbidity (TD) and dissolved oxygen (DO). Hemiptera abundance increases with decreasing DO; Ostracoda abundance increases with increasing EC and TD and the decrease in DO; and Trichoptera abundance increases with the decrease in EC and TD and the increase in DO. The stretches exhibited similarity in relation to the richness and abundance of macroinvertebrates and limnological parameters. The macroinvertebrates distribution in the stream not showed the same pattern, grouping s.u. of different stretch, because the habitat structural variables influenced the distribution. CONCLUSIONS: Therefore, the macroinvertebrates community varies according to abiotic factors in different limnological and structural parameters. This study is the first record of a work that associates benthic fauna and abiotic parameters at the Atlantic forest of Pernambuco.